44th AIAA Aerospace Sciences Meeting and Exhibit 2006
DOI: 10.2514/6.2006-301
|View full text |Cite
|
Sign up to set email alerts
|

High-Order Multidomain Spectral Difference Method for the Navier-Stokes Equations

Abstract: A high order multidomain spectral difference (SD) method is developed for the three dimensional Navier-Stokes equations on unstructured hexahedral grids. The method is easy to implement since it involves one-dimensional operations only, and does not involve surface or volume integrals. Universal reconstructions are obtained by distributing solution and flux points in a geometrically similar manner in a unit cube. The concepts of the Riemann solver and high-order local representations are applied to achieve con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
158
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(173 citation statements)
references
References 26 publications
(39 reference statements)
1
158
0
1
Order By: Relevance
“…In contrast to DG schemes (for which the treatment of viscous terms is somewhat involved), SD type schemes are able to accommodate viscous terms in a simple fashion [123]. The FR approach potentially offers an equally simple way to treat viscous terms [59].…”
Section: Flux Reconstruction For Viscous Termsmentioning
confidence: 99%
“…In contrast to DG schemes (for which the treatment of viscous terms is somewhat involved), SD type schemes are able to accommodate viscous terms in a simple fashion [123]. The FR approach potentially offers an equally simple way to treat viscous terms [59].…”
Section: Flux Reconstruction For Viscous Termsmentioning
confidence: 99%
“…The formulation of the equations for the 2D spectral difference scheme on quadrilateral meshes is similar to the formulation of Sun et al 3 for unstructured hexahedral grids Consider the unsteady compressible 2D Navier Stokes equations in conservative form…”
Section: Formulation Of 2d Spectral Difference Scheme On Quadrilamentioning
confidence: 99%
“…2,3 Even though this approach is easy to implement, the computational effort involved is large since each variable at each solution point has to be changed, and the residuals recomputed. Numerical tests have shown that it is not necessary to compute the Jacobian matrix at every iteration.…”
Section: Implicit Schemementioning
confidence: 99%
See 1 more Smart Citation
“…The solver, which is based on the approach presented by Wang [19], can run on meshes containing both straight-sided and curved-sided quadrilateral elements. An methodology for applying the code to unstructured mixed meshes containing both triangular and quadrangular elements has also been developed [20].…”
Section: Code Development 231 Two-dimensional Compressible Viscous mentioning
confidence: 99%